Expectativa e experiência de parto em uma maternidade signatária do projeto parto adequado - Barbosa, Luara de Carvalho (2019)
Although in recent years, based on science and politics evidences, we have experienced an important change in the obstetric scenario in Brazil, there is still a gap in care practice, which favors the medicalization of the female body and birth, as well as the inequality of gender and violence against women. The “Projeto Parto Adequado”, supported by the Ministry of Health, which aims to implement improved delivery and childbirth care in private and public hospitals, has been adopted by institutions in order to improve the quality of services, valuing normal childbirth and minimizing negative outcomes for women and infants, as well as providing a satisfactory experience for women. The present study aimed to understand the influence of the Adequate Childbirth Project on the experience of normal birth for women. The Política Nacional de Humanização (PNH) and the Good Practices of Attention to Childbirth and “Boas Práticas de Atencao ao Parto e ao Nascimento”, based on the theory of social representations and as a methodological reference the analysis of thematic content. The data collection took place in a city of the state of Sao Paulo, from January to March 2018 in two stages: in the first one (quantitative part of the research) the “Technique of Free Association of Words with the term “vaginal birth” was applied to 62 pregnant women at their first prenatal hospital visit, and in the second stage (qualitative part), with tracing the deliveries of women in the first stage, 18 puerperal women were individually interviewed with the triggering statement: “Tell me about your experience in maternity”. For the analysis of the material was used, in the first stage the software OpenEvoc and for the second, the software Iramuteq. The analysis of the empirical data allowed to identify that pain, marvelous, recovery, anxiety, desires, love and expectation were part of the central nucleus of the apprehension of women on normal birth and later the experiences were transcribed and treated according to a double criterion of analysis: Lexical Analysis - Word Cloud and 2. Thematic Content Analysis. As the main theme “The Transition of Care Model” and 03 thematic categories: “Surprising model”, “Model that satisfies” and “Model with embarrassments”. Although women have shown an important influence of the Adequate Childbirth Project, women bring notes of still good practices are not completely instituted, as well as demonstrate that they lack to be heard and / or valued. Thus, one realizes that only one policy or one program would not be sufficient to change a reality so concretized. It is necessary to rethink mechanisms that re-signify birth to society, as well as a vocational training path that values gender issues, and a care free of physical and emotional harm.